Knickerwallahs, silly - Billies and other curious creatures - Aiyar, Mani Shankar (New Delhi, 1995)
This volume presents a pithy and thought-provoking collection of his characteristically racy, incisive and, sometimes, prophetic articles gleaned from a variety of sources on a diverse range of topics.
Keywords: Rashtriya sawayamsewak sang